An Undergraduate Guide to Analog and Digital Communication Principles - Nadiatulhuda Zulkifli; Nor Hafizah Ngajikin (2025)
This book targets undergraduate students and individuals interested in the field, offering a solid foundation in analog and digital communication systems. Key topics covered include amplitude modulation, angle modulation, pulse modulation, binary shift keying, multi-level modulation, generation and detection of analog and digital modulated signals, noise, bit error probabilities, and multiplexing. Beyond the fundamentals, the book introduces readers to applications involving recent technologies like 5G and IoT, ensuring they stay abreast of the latest advancements. The book provides an engaging learning experience with MATLAB guides, examples, exercises, and model final-year exam questions for each chapter. Addressing engineers' responsibilities, it also discusses communication technology's broader impacts on society, encompassing economic, environmental, health, and security considerations. By imparting essential knowledge and skills, this textbook prepares readers to excel in the dynamic field of communication engineering and understand its profound global influence.